2014
DOI: 10.1016/j.dhjo.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Key goals and indicators for successful aging of adults with early-onset disability

Abstract: Substantial improvements have occurred in the longevity of several groups of individuals with early-onset disabilities, with many now surviving to advanced ages. This paper estimates the population of adults aging with early-onset disabilities at 12-15 million persons. Key goals for the successful aging of adults with early-onset disabilities are discussed, emphasizing reduction in risks for aging-related chronic disease and secondary conditions, while promoting social participation and independence. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…Low probability of disease and diseaserelated disability in people with an intellectual disability Key indicators for successful ageing in intellectual disability include good physical and mental health, healthy lifestyles and behaviours, social interaction and productivity, life satisfaction, and access to quality healthcare [17]. A strategy for successful ageing in intellectual disability is to focus on modifiable or even preventable conditions that have been found to be predictors of successful ageing in healthy older adults like smoking and avoiding obesity.…”
Section: Key Pointsmentioning
confidence: 97%
“…Low probability of disease and diseaserelated disability in people with an intellectual disability Key indicators for successful ageing in intellectual disability include good physical and mental health, healthy lifestyles and behaviours, social interaction and productivity, life satisfaction, and access to quality healthcare [17]. A strategy for successful ageing in intellectual disability is to focus on modifiable or even preventable conditions that have been found to be predictors of successful ageing in healthy older adults like smoking and avoiding obesity.…”
Section: Key Pointsmentioning
confidence: 97%
“…This is often attributed to the demographic trend that it has only been in past decades that groups of people with extensive or lasting disabilities have been able to live long lives and reach what is thought of as "old age" (Agree, 2014). Due to advancements in welfare and medicine, many people with earlyonset disabilities can now live longer than in the past (Naidoo, Putnam & Spindel, 2012;LaPlante, 2014). This group, as well as younger generations of people with disabilities, now have the possibility to "experience the benefits and challenges of ageing in adulthood", which may include higher education, family building, career, and an active old age (LaPlante, 2014).…”
Section: Ageing With Disabilitymentioning
confidence: 99%
“…The disability processes related to ageing are also well-researched, but not the pathways of the people growing old with these disabilities (Agree, 2014). Thus, recent works that try to fill this gap refer to the important distinction between research on "ageing with disability", which is still underexplored, and research on "ageing into disability" that has characterized the majority of previous works on impairments and high age (Yorkston et al, 2010;Washko, Campbell & Tilly, 2012;LaPlante, 2014;Monahan & Wolf, 2014). A literature search I conducted in Scopus on "ageing with disability" showed that while earlier texts primarily dealt with the medical dimensions of disability such as rehabilitation, recent publications, especially in the past three years, have begun to look at "ageing with disability" as a modern phenomenon in itself with biographical, social, and policy dimensions.…”
Section: Ageing With Disabilitymentioning
confidence: 99%
See 2 more Smart Citations